Law's ideal dimension - Alexy, Robert (Oxford : Oxford University Press, 2021)
This collection provides a comprehensive account of Robert Alexy's legal theory. It is divided into three parts: the nature of law; constitutional rights, human rights, and proportionality; and the relation between argumentation, correctness, and law.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 7, 2021).
Keywords: Law -- Philosophy; Human rights -- Philosophy; Constitutional law -- Philosophy